The Real Costs of Financial Efficiency When Some Information Is Soft - Edmans, Alex; Heinle, Mirko S.; Huang, Chong (Review of Finance, 2016)
This article shows that improving financial efficiency may reduce real efficiency. While the former depends on the total amount of information available, the latter depends on the relative amounts of hard and soft information. Disclosing more hard information (e.g., earnings) increases total information, raising financial efficiency and reducing the cost of capital. However, it induces the manager to prioritize hard information over soft by cutting intangible investment to boost earnings, lowering real efficiency. The optimal level of financial efficiency is non-monotonic in investment opportunities. Even if low financial efficiency is desirable to induce investment, the manager may be unable to commit to it. Optimal government policy may involve upper, not lower, bounds on financial efficiency.